PERSEPSI MASYARAKAT TENTANG ECOBRICK DI DUSUN WAINUSALAUT NEGERI SULI KABUPATEN MALUKU TENGAH - Tuapattinaya, Prelly M. J.; Rehena, J F; Laisina, Agustina (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2022)
Background: Awareness of the environmental impact of waste continues to grow and effective waste management is currently a key target in environmental policies around the world, because of how the waste that is managed directly affects the local environment and global quality.Methods: The research was conducted in the State of Suli, RT 048 Dusun Wainusalaut. The type of research used is descriptive.Results: The results showed that indicators 1 to 3 with 10 questions received very good responses and appreciation through strongly agree and agree to answers.Conclusion: The community considers that eco-bricks are a method of reducing plastic waste that is very practical and easy and very good to make. Apart from being a creative activity,eco-bricks are also very useful and economical if practiced properly.